Computing, Brains and Geophysics? - Pethick, Andrew; Harris, Brett; Lam, K. (CSIRO, 2013)
Brain computer interface (BCI) systems emerging as a breakthrough technology of the 21st century. As is the case with other developing technologies, proof of concept must be demonstrated before advanced methods are pursued. This article presents the first published case study of a brain controlled geophysical software package. We show how brain computer interface systems can facilitate accelerated learning in the geoscience community. Our results show that processed brainwaves from the NeuroSky MindWave electroencephalography (EEG) device can be used to control various geophysical survey parameters with an acceptable degree of accuracy and to model the corresponding data in real-time.